Kesiapan Guru Taman Kanak-Kanak dalam Mengimplementasikan Pendekatan Deep Learning di Kecamatan Cijeungjing Kabupaten Ciamis - Hindayanti, Rosma Bella; Rahman, Taopik; Sianturi, Risbon (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
The limited implementation of the deep learning approach in early childhood education, particularly in Cijeungjing, Ciamis Regency, has become a key concern in efforts to improve the quality of learning. This approach is believed to enrich the learning process by integrating mindful, meaningful, and joyful learning. This study aims to assess kindergarten teachers’ readiness to implement the deep learning approach, based on four dimensions of the readiness for change theory: appropriateness, change efficacy, management support, and personal benefit. A quantitative descriptive method was employed using a survey involving 68 teachers from various early childhood education institutions. The analysis revealed that all readiness dimensions were categorized as high: management support (76.4%), appropriateness (74.6%), change efficacy (74.2%), and personal benefit (70.0%). These findings indicate that early childhood teachers in the region possess both psychological and structural readiness to adopt deep learning-based instructional innovations. The study implies the importance of continuous training and mentoring to holistically strengthen teachers' readiness in supporting 21st-century learning transformation.